2016
DOI: 10.1161/jaha.115.002756
|View full text |Cite
|
Sign up to set email alerts
|

Primary Prevention Implantable Cardioverter Defibrillator (ICD) Therapy in Women—Data From a Multicenter French Registry

Abstract: BackgroundThere are limited data describing sex specificities regarding implantable cardioverter defibrillators (ICDs) in the real‐world European setting.Methods and ResultsUsing a large multicenter cohort of consecutive patients referred for ICD implantation for primary prevention (2002–2012), in ischemic and nonischemic cardiomyopathy, we examined the sex differences in subjects' characteristics and outcomes. Of 5539 patients, only 837 (15.1%) were women and 53.8% received cardiac resynchronization therapy. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
48
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 39 publications
4
48
0
Order By: Relevance
“…In a large multicentre French registry, women who had ICD implantation for primary prevention had a significantly lower likelihood of receiving appropriate ICD therapies (17.4% vs 23%, P<0.001) but had similar mortality compared with men (HR=0.87, 95% CI 0.66 to 1.15, P=0.324) 21. There was no gender difference observed with inappropriate shocks (6.7% vs 6.7%, OR 1.0, 95% CI 0.74 to 1.35, P=0.997) 21. Similarly, Seegers et al 22 showed that women received 50% less appropriate ICD shocks than men (3.6% vs 6.3% per year, P=0.002), although both groups have similar mortality (P=0.08).…”
Section: Discussionmentioning
confidence: 99%
“…In a large multicentre French registry, women who had ICD implantation for primary prevention had a significantly lower likelihood of receiving appropriate ICD therapies (17.4% vs 23%, P<0.001) but had similar mortality compared with men (HR=0.87, 95% CI 0.66 to 1.15, P=0.324) 21. There was no gender difference observed with inappropriate shocks (6.7% vs 6.7%, OR 1.0, 95% CI 0.74 to 1.35, P=0.997) 21. Similarly, Seegers et al 22 showed that women received 50% less appropriate ICD shocks than men (3.6% vs 6.3% per year, P=0.002), although both groups have similar mortality (P=0.08).…”
Section: Discussionmentioning
confidence: 99%
“…The remaining 5307 patients represent the study group—4037 (76.1%) received CRT-D (all primary prevention), while the remaining 1270 (23.9%) received CRT-P. Most patients from our cohort have been included and described in more detail in previous studies 5 6 8 9. Ischaemic cardiomyopathy was defined as the presence of systolic dysfunction associated with a history of myocardial infarction and/or the presence of significant coronary artery disease documented on a coronary angiogram.…”
Section: Methodsmentioning
confidence: 99%
“…In the Défibrillateur Automatique Implantable en Prévention Primaire (DAI-PP) registry8 and CeRtiTuDe cohort study,5 vital status data were obtained from the hospital or the general practitioner, and were systematically controlled through the National Institute of Statistics Economical Studies. Causes of death were obtained by the investigators and/or by the French Center on Medical Causes of Death (CepiDc–INSERM).…”
Section: Methodsmentioning
confidence: 99%
“…We further compared this cohort with a control group of 95 patients with pacing-induced cardiomyopathy and no history of sustained ventricular arrhythmias receiving an upgrade to CRT-D. The latter group was included in the DAI-PP study (Defibrillateur Automatique Implantable Prevention Primaire; NCT01992458) (13). We hypothesised that patients with pacing-induced cardiomyopathy could be safely upgraded to a CRT-P device only.…”
Section: Methodsmentioning
confidence: 99%
“…Briefly, this was a registry on 5,539 patients implanted with an ICD (with or without CRT) in the setting of primary prevention in 12 French centers (13). Our control group included all patients with no history of coronary artery disease or any underlying cardiomyopathy who had an upgrade of pacemaker to CRT-D due to LV systolic function deterioration deemed to be the result of chronic RV pacing.…”
Section: Patients' Eligibility Criteria Procedural Details and Follomentioning
confidence: 99%